Functional marker development of miR1511-InDel and allelic diversity within the genus Glycine - Htwe, Nang Myint Phyu Sin (BMC Genomics, 2015)
BACKGROUND: Single-stranded non-protein coding small RNAs, 18–25 nucleotides in length, are ubiquitous throughout plants genomes and are involved in post-transcriptional gene regulation. Several types of DNA markers have been reported for the detection of genetic diversity or sequence variation in soybean, one of the most important legume crops in worldwide for seed protein and oil content. Recently, with the available of public genomic databases, there has been a shift from the labor-intensive development of PCR-based markers to sequence-based genotyping and the development of functional markers within genes, often coupled with the use of RNA information. But thus far miRNA-based markers have been only developed in rice and tobacco. Here we report the first functional molecular miRNA marker, miR1511-InDel, in soybean for a specific single copy locus used to assess genetic variation in domesticated soybean (Glycine max [L.] Merr) and its wild progenitor (Glycine soja Sieb. & Zucc.). RESULTS: We genotyped a total of 1,669 accessions of domesticated soybean (G. max) and its wild progenitor G. soja which are native throughout the China and parts of Korea, Japan and Russia. The results indicate that the miR1511 locus is distributed in cultivated soybean and has three alleles in annual wild soybean. Based on this result, we proposed that miR-InDel marker technology can be used to assess genetic variation. The inclusion of geo-reference data with miR1511-InDel marker data corroborated that accessions from the Yellow River basin (Huanghuai) exhibited high genetic diversity which provides more molecular evidence for gene diversity in annual wild soybean and domestication of soybean. CONCLUSIONS: These results provide evidence for the use of RNA marker, miRNA1511-InDel, as a soybean-specific functional maker for the study of genetic diversity, genotyping of germplasm and evolution studies. This is also the first report of functional marker developed from soybean miRNA located within the functional region of pre-miRNA1511. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-015-1665-3) contains supplementary material, which is available to authorized users.